Process for the manufacture of ultra-low dielectric loss electronic grade glass fiber cloth
Patent Information
- Application Number
- CN202611329850.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-23
AI Technical Summary
[0003]中国专利CN115354494A公开一种薄型电子级玻璃纤维布的生产方法,将电子级玻璃纤维纱进行上浆处理,将浆料均匀涂抹在每根玻璃纤维纱的纱线上,将玻璃纤维纱缠绕在经轴上,进行整浆;将整浆完成后浆好的玻璃纤维纱用喷气织布机织成薄型玻璃纤维布;将织好的薄型玻璃纤维布进行一次高温退浆,将一次高温退浆后的薄型玻璃纤维布进行二次高温退浆,浆料残留量退至0.05%以下,得到退浆后的薄型玻璃纤维布;将退浆后的薄型玻璃纤维布进行开纤,将开纤后的玻璃纤维布经表面处理剂硅烷偶联剂的浸渍处理,得到薄型电子级玻璃纤维布,制备得到的电子级玻璃纤维布布面平整且满足薄型纤维布厚度要求;但是该专利中两次热处理均为高温热处理,且一次高温热处理过程中可燃物燃烧过程中产生的热量易造成玻璃纤维强度的损失,导致布面质量差,毛丝量大,生产的玻璃纤维布介电性能差
(1)本发明通过控制玻璃坯布在一次热处理后的水分含量、可燃物含量以及透气度,配合二次热处理分阶段加热排除水分和残余浆料,可使超低介电损耗电子级玻璃纤维布的介电损耗(10GHz)在0.0007以下,适配多种应用场景。
Smart Images

Figure SMS_5 
Figure SMS_6
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fiber surface treatment technology, specifically relating to a manufacturing process for ultra-low dielectric loss electronic-grade glass fiber cloth. Background Technology
[0002] High-end electronic products such as 5G communication equipment, intelligent robot equipment, digital medical equipment, and wearable electronic devices are rapidly developing towards miniaturization, thinning, and high performance, which puts forward higher requirements for the performance of electronic glass fiber yarn and its products, which are the core substrates of printed circuit boards (PCBs). The continuous upgrading of PCBs towards higher component density, smaller size, and higher integration directly promotes the development of glass fiber cloth with characteristics such as low loss and low expansion coefficient.
[0003] Chinese patent CN115354494A discloses a method for producing thin electronic-grade glass fiber cloth. The method involves sizing electronic-grade glass fiber yarn by evenly applying sizing agent to each yarn, winding the yarn onto a warp beam, and then sizing again. The sized glass fiber yarn is then woven into thin glass fiber cloth using an air-jet loom. The woven thin glass fiber cloth undergoes a first high-temperature desizing, followed by a second high-temperature desizing until the residual sizing agent content is reduced to below 0.05%. Thin glass fiber cloth after desizing; the desizing thin glass fiber cloth is split, and the split glass fiber cloth is impregnated with a surface treatment agent, silane coupling agent, to obtain thin electronic-grade glass fiber cloth. The prepared electronic-grade glass fiber cloth has a smooth surface and meets the thickness requirements of thin fiber cloth; however, both heat treatments in this patent are high-temperature heat treatments, and the heat generated during the combustion of combustibles in the first high-temperature heat treatment process can easily cause a loss of glass fiber strength, resulting in poor cloth quality, large amount of fuzz, and poor dielectric properties of the produced glass fiber cloth. Summary of the Invention
[0004] The purpose of this invention is to provide a manufacturing process for ultra-low dielectric loss electronic-grade glass fiber cloth, which produces glass fiber cloth with excellent dielectric properties and fabric surface quality, and avoids the formation of white spots when coating with silane coupling agents.
[0005] The manufacturing process of the ultra-low dielectric loss electronic-grade glass fiber cloth of the present invention includes the following steps: (1) Glass fiber yarn is sized and woven to obtain glass fabric; (2) The glass blank is heat-treated once to obtain glass fiber cloth I; (3) Glass fiber cloth I undergoes secondary heat treatment to obtain glass fiber cloth II; (4) Glass fiber cloth II is washed and split, and then silanized to obtain ultra-low dielectric loss electronic grade glass fiber cloth.
[0006] The ultra-low dielectric loss electronic-grade glass fiber cloth has a SiO2 content greater than 99.9 wt% and a dielectric loss (10 GHz) of 0.0004-0.0007.
[0007] In step (1), the fiberglass yarn is obtained by coating the fiberglass with a sizing agent and then twisting and winding it. The sizing agent includes starch, softener, lubricant and bundler.
[0008] In step (1), the combustible content in the glass blank is about 5 wt% (4.5-5.5 wt%), and the combustibles include polyvinyl alcohol (PVA) and starch; the sizing rate is 1-7%, which can be adjusted by the sizing tension and curling speed during sizing.
[0009] After the woven glass fabric is curled, organic matter adheres to its surface, resulting in poor dielectric properties that affect the adhesion of the silane coupling agent to the surface of the glass fabric. If the adhered slurry and impregnating agent are removed directly by high-temperature combustion, the strength of the glass fabric will be significantly reduced. Therefore, the glass fabric is first subjected to a heat treatment.
[0010] In step (2), the combustible content of fiberglass cloth I is 0.1-1.0 wt%, and the combustibles include polyvinyl alcohol and starch; the moisture content of fiberglass cloth I is 0.01-0.5 wt%, and the air permeability is 30-100 cm. 3 / cm 2 / s.
[0011] In step (2), the heat treatment consists of sequential cleaning and drying. The cleaning process involves sequential oscillating water washing and high-pressure water jet cleaning. The oscillating water washing speed is 100-300 rpm, the water temperature is 30-60℃, and the washing time is 2-20 seconds. The high-pressure water jet cleaning speed is 20-25℃, the washing time is 10 seconds, and the pressure is 1.0-5.0 kgf / cm². 2 The drying temperature is 30-80℃, the drying time is 20-30s, and the moving speed of the glass blank cloth during cleaning and drying is 40-50m / min.
[0012] High-pressure water jet cleaning can remove organic matter such as PVA from the surface of the glass fabric and also open the fibers of the glass fabric. The drying heating method includes at least one of drum drying, natural gas heating drying, or coal gas heating drying. The drying temperature is 30-80℃, which can avoid problems such as wrinkling and deformation of the glass fabric during the drying process.
[0013] In step (2), the moisture content of glass fiber cloth I is 0.01-0.50 wt%. Moisture can cause the silicon-oxygen bridges in the glass fiber to undergo hydrolysis. The breakage of Si-O-Si will cause microcracks on the fiber surface, which will reduce the strength of the glass fiber. Therefore, in order to ensure product performance, the moisture content of glass fiber cloth I is controlled at 0.01-0.50wt%, preferably 0.01-0.10wt%.
[0014] In step (2), the combustible content of fiberglass cloth I is 0.1-1.0 wt%. During the first heat treatment, the combustible content can be controlled by changing the temperature of the oscillating water washing or the pressure of the high-pressure water jet cleaning. If the combustible content is too low, a large number of wrinkles and fuzz will appear on the surface of fiberglass cloth I, which will affect the quality of the final product. If the combustible content is too high, a large amount of heat will be released instantly during the second heat treatment, causing damage to the surface structure of the fiberglass and a decrease in strength. Therefore, in order to ensure product performance, the combustible content of fiberglass cloth I is controlled to be 0.1-1.0 wt%.
[0015] The air permeability of fiberglass cloth I is 30-100cm. 3 / cm 2 Low air permeability can lead to oxygen-deficient combustion of organic matter during secondary heat treatment, leaving residual carbon and resulting in increased dielectric loss and damaged fiber strength. Conversely, excessive air permeability significantly increases the contact area between the fiber and air and impurities, which is also detrimental to the stability of dielectric properties. Therefore, the air permeability of fiberglass cloth I is controlled at 30-100 cm² / s. 3 / cm 2 / s, preferably 50-70cm 3 / cm 2 / s.
[0016] The total time for the secondary heat treatment in step (3) is 50-120 hours. The secondary heat treatment is carried out in four stages. Taking the sum of the heating amount of the four stages as 100%, the heating amount of each stage is as follows: the heating amount of the first stage (Q1) is 10-20%, the heating amount of the second stage (Q2) is 5-15%, the heating amount of the third stage (Q3) is 20-50%, and the heating amount of the fourth stage (Q4) is 40-60%. The heating amount is the integral value of the heating temperature over time, and the unit of heating amount is ℃·h.
[0017] The first stage is the heating stage, with a heating temperature of 130-150℃; the second stage is the heat preservation stage, with the heat preservation temperature being the same as the heating temperature in the first stage.
[0018] The third stage is the heating stage, with a heating temperature of 300-650℃; the fourth stage is the heat preservation stage, with the heat preservation temperature being the same as the heating temperature in the third stage.
[0019] The heating amount is represented by the integral area of the temperature-time curve, and the calculation formula is as follows: , Where Q is the heating amount (°C·h). T represents the heating temperature (°C). t represents time (h). t0 is the heating start time for the corresponding stage. t f This represents the heating termination time for the corresponding stage.
[0020] The residual slurry on the surface of the glass fabric has water-absorbing properties, and the moisture can cause hydrolysis of the silicon-oxygen bridges in the glass fibers. This leads to the formation of silanol groups on the fiber surface. The formation of silanol groups includes three stages: water molecule adsorption, chemical bond breaking, and hydroxyl group recombination. Reducing the H2O content in the system can shift the equilibrium of the above hydrolysis reaction to the left, effectively inhibiting the formation of Si-OH. The lower the Si-OH content on the surface of the glass fiber cloth, the lower its dielectric loss will be.
[0021] After sizing, weaving, and initial heat treatment, glass fibers still retain a small amount of organic matter such as starch and PVA on their surface. If these organic substances are not completely degraded during the secondary heat treatment, they will remain on the surface, affecting the subsequent coating of silane coupling agents. This leads to poor bonding between the glass fiber cloth and the resin, resulting in decreased stability of the PCB substrate. Glass fibers are composed of a [SiO4] tetrahedral network structure, exhibiting a low coefficient of thermal expansion, good dielectric properties, and high chemical stability. However, the strength of glass fibers decreases significantly with increasing temperature. Furthermore, an excessively low coefficient of thermal expansion can cause tearing, fiber breakage, or poor flexibility in the glass fiber cloth during the silane coupling agent coating process, affecting production efficiency and fabric quality.
[0022] Glass fiber is composed of a [SiO4] tetrahedral network structure, which has a small coefficient of thermal expansion. The strength of glass fiber decreases significantly with increasing temperature, and the faster the heating rate, the faster the strength decays. Therefore, the heating rate in the first stage is set to 1-10℃ / min, preferably 2-5℃ / min. The organic matter attached to the surface of glass fiber cloth I undergoes a dehydration and etherification reaction at 100-200℃. However, the activation energy required for the hydrolysis of silicon-oxygen bridges in the glass fiber to generate Si-OH is insufficient below 150℃. Therefore, to achieve dehydration and etherification of the organic matter while inhibiting Si-OH formation, the heating temperature in the first stage is 130-150℃, i.e., from room temperature to 130-150℃, preferably 130℃, with the heating amount in the first stage accounting for 10-20%. The holding temperature in the second stage is the same as the heating temperature in the first stage, i.e., 130-150℃, preferably 130℃, with the heating amount in the second stage accounting for 5-15%, preferably 10%.
[0023] Glass fiber has a low coefficient of thermal expansion. If the temperature rises too quickly during the secondary heat treatment, a temperature difference easily forms between the inside and outside of the fiber, generating significant thermal stress. This leads to a decrease in the mechanical strength of the glass fiber and an increase in the number of fuzzy fibers on the fabric surface. The first derivative (weight loss rate) of the PVA and starch substances attached to the glass fiber surface begins to increase significantly at 300℃ and reaches its maximum value at 420℃. The more complete the combustion of organic matter, the lower the dielectric loss. To ensure that the finished glass fiber cloth has both minimal strength loss and low dielectric loss, the heating temperature of the third stage is limited to 300-650℃, preferably 300-500℃, and the heating rate is set to 0.5-5℃ / min, preferably 1-2℃ / min. The heating amount accounts for 20-50%, preferably 20-30%. The heating temperature of the fourth stage is the same as that of the third stage, i.e., 300-650℃, preferably 300-500℃, and the heating amount of the fourth stage accounts for 40-60%.
[0024] The amount of Si-OH generated on the glass fiber surface and the content of organic matter adhering to the glass fiber surface both affect the dielectric loss of the final glass fiber cloth. The proportion of heating at each stage determines the heat input intensity and residence time of the glass fiber cloth in the corresponding temperature range, thus affecting the quality and performance of the final glass fiber cloth product. Therefore, limiting the proportion of heating at each stage can ensure the quality of the fabric surface while suppressing hydroxyl group formation and fully removing combustibles, ultimately obtaining a glass fiber cloth with low dielectric loss.
[0025] The moisture content in the heating gas for the secondary heat treatment in step (3) is 0.01-0.10 wt%.
[0026] The secondary heat treatment is carried out in a heating furnace at a temperature of 100-650℃, with the following heating control parameters: The moisture content in the heating gas is 0.01-0.10 wt%. The heating gas is introduced 1 hour before the first stage of heating. The flow rate of the heating gas is 2-10 m³ / h. 3 / min.
[0027] Furthermore, based on the principle of hydroxyl group formation: The lower the moisture content, the fewer hydroxyl groups are formed, and the lower the dielectric loss of the glass fiber cloth. Therefore, a gas with a moisture content of 0.01-0.10 wt% is selected as the heating gas. In order to obtain glass fiber cloth II with low combustible content and low hydroxyl content, air is preferred as the heating gas, and dry air with a moisture content of 0.01-0.05 wt% is more preferred.
[0028] In step (4), the fiber opening process involves sequentially performing a first-time and a second-time water washing process.
[0029] The pH of the washing solution in the first water washing and fiber opening process is 7-9, and the pH of the washing solution in the second water washing and fiber opening process is 4-5.
[0030] In glass, SiO2 forms a silicon-oxygen tetrahedral structure and further constitutes a three-dimensional network framework. When the SiO2 content in the glass is high, the three-dimensional network framework is denser and more continuous, resulting in stronger resistance to chemical corrosion. However, this also leads to higher chemical inertness on the fiber surface, making it difficult for the silane coupling agent to wet and spread on the glass fiber surface. Therefore, white spots are easily generated on the surface of the glass fiber cloth during subsequent production processes, resulting in poor bonding between the glass fiber cloth and the matrix resin. The surface roughness of the glass fiber directly affects its specific surface area. The greater the surface roughness, the larger the specific surface area, and the greater the wettability of the silane coupling agent on the glass fiber surface. This invention increases the surface roughness of the glass fiber by controlling the pH of the washing solution during the fiber opening process, thereby improving the wettability of the silane coupling agent on the glass fiber surface and thus improving the bonding stability with the resin matrix.
[0031] A high pH in the washing solution will significantly reduce the strength of the glass fiber. Therefore, the pH of the washing solution for the first washing and fiber opening should be 7-9, preferably 8-9. Glass fibers and the organic matter remaining on their surface are hydrophobic, and the fibers themselves have a high charge density, making them prone to adsorption and aggregation in the washing solution, resulting in poor fiber dispersion. Lowering the pH of the washing solution can change the charge distribution on the fiber surface, increase the electrostatic repulsion between fibers, and facilitate fiber spreading and dispersion. Therefore, the pH of the washing solution for the second washing and fiber opening should be 4-5. During the washing and fiber opening process, the moving speed of the glass fiber cloth II should be controlled at 40-50 m / min.
[0032] Glass fiber is formed by a [SiO4] tetrahedral network structure, containing many bridging oxygen bonds, exhibiting strong chemical structural stability and hydrophobicity. However, the fiber surface has low reactivity and poor adhesion of coupling agents. Directly coating the surface of glass fiber cloth II with silane coupling agents can lead to uneven coating and the formation of white spots. This invention addresses this problem through a two-stage water washing and fiber opening process: under the weakly alkaline water washing conditions of the first water washing and fiber opening stage, the SiO2 on the glass fiber surface... - Under the action of the agent, the silicon-oxygen bond breaks, the fiber surface is subjected to controlled erosion, the surface roughness and specific surface area increase, the adsorption is enhanced, which can improve the wettability of the silane coupling agent on the fiber surface, making the silane coupling agent coating more uniform and reducing the occurrence of white spots on the fabric surface; the weak acidic water washing of the second water washing and fiber opening can improve the uniformity of fiber dispersion, further ensuring the uniformity of silane coupling agent coating, and together reducing the white spot defect on the surface of glass fiber cloth.
[0033] The surface of the glass fiber cloth II obtained after glass fiber desizing (primary and secondary heat treatments) is weakly alkaline. If pure water with a pH of 6-7 is used for washing and fiber opening, the alkaline components cannot be effectively removed. During continuous production, the pH of the silane coupling agent will increase, leading to premature deactivation of the silane coupling agent. This invention, by precisely controlling the pH value of the washing solution in stages during the fiber opening process, can significantly extend the effective service life of the silane coupling agent compared to the pure water fiber opening process.
[0034] In step (4), the dielectric loss of the ultra-low dielectric loss electronic-grade glass fiber cloth at 10 GHz is 0.0004-0.0007.
[0035] In step (4), during the silanization treatment, it is preferable to prepare a uniformly dispersed aqueous solution of the silane coupling agent with a concentration of 0.02-0.05 wt%. To ensure the complete hydrolysis and uniform dispersion of the silane coupling agent, a pH adjuster needs to be added to the aqueous solution of the coupling agent to adjust the pH to 1-3, preferably 2-3. The pH adjuster is preferably acetic acid. The silane coupling agent includes one of methacryloyloxypropyltrimethoxysilane (KH-570), methacryloyloxypropyltrichlorosilane, vinyltriacetoxysilane, or chloromethyltriethoxysilane, preferably methacryloyloxypropyltrimethoxysilane.
[0036] In the silanization process, the moving speed of glass fiber cloth II is a key process control point, which is the same as the moving speed of glass fiber cloth II during water washing and fiber opening, i.e., 40-50 m / min. When the cloth speed is lower than 40 m / min, the surface roughness of the glass fiber cloth is too large, which will cause the silane coupling agent to lag in wetting on the glass fiber surface and be unevenly dispersed, thereby affecting the strength of the interface between the glass fiber cloth and the resin and reducing the strength of the ultra-low dielectric loss electronic grade glass fiber cloth. When the cloth speed is higher than 50 m / min, it is difficult to achieve the fiber opening effect. The silane coupling agent cannot be evenly coated on the glass fiber surface, resulting in white spots. The strength recovery of the ultra-low dielectric loss electronic grade glass fiber cloth is small, and the impregnation time of the ultra-low dielectric loss electronic grade glass fiber cloth in the resin is long, which also leads to low efficiency in the subsequent resin bonding process.
[0037] The beneficial effects of this invention are as follows: (1) By controlling the moisture content, combustible content and air permeability of the glass blank after the first heat treatment, and by using the second heat treatment to remove moisture and residual slurry in stages, the dielectric loss (10GHz) of the ultra-low dielectric loss electronic grade glass fiber cloth can be below 0.0007, making it suitable for a variety of application scenarios.
[0038] (2) In the preparation of the ultra-low dielectric loss electronic-grade glass fiber cloth in this invention, white spots can be avoided during the silanization process, ensuring uniform bonding between the ultra-low dielectric loss electronic-grade glass fiber cloth and the resin interface, improving the mechanical properties and dielectric stability of the composite material; at the same time, it can extend the service time of the silane coupling agent, effectively reduce the cost of industrial production, and improve the efficiency of continuous production.
[0039] (3) The present invention prepares ultra-low dielectric loss electronic-grade glass fiber cloth through three processes: primary heat treatment, secondary heat treatment, and two-stage pH-controlled water washing and fiber opening. The first heat treatment removes free moisture and volatile sizing components from the glass fiber fabric, reducing the heat load of the subsequent second heat treatment and minimizing the formation of moisture-induced silanol groups. The second heat treatment employs a staged heating ratio process, relying on thermal oxidation to deeply remove residual organic sizing and moisture, while simultaneously alleviating thermal stress in the low-expansion glass fibers and preventing fiber fuzzing and deterioration of mechanical strength. The fibers in the glass fiber fabric II obtained after the second heat treatment are prone to mutual adsorption and aggregation, and the fiber surface is chemically inert and has trace amounts of alkaline substances attached. Therefore, a two-stage differentiated pH water washing and fiber opening process is set up: a weakly alkaline water washing tank performs controllable micro-etching on the fiber surface to improve surface roughness and enhance the wettability of the silane coupling agent, fundamentally preventing white spots from appearing during silanization treatment; a weakly acidic water washing tank achieves full fiber opening through electrostatic repulsion and neutralizes the alkaline components on the fabric surface, preventing the subsequent silane coupling agent aqueous solution from prematurely failing due to abnormal pH increases. The three processes are interconnected and complementary. While thoroughly removing the sizing agent and ensuring low dielectric loss and mechanical strength of the fiber cloth, the process optimizes the surface interface of the fiber, improves the bonding stability between the fiber cloth and the matrix resin, reduces the cost of downstream chemical consumables, and enhances the stability of mass production processing. Detailed Implementation
[0040] The present invention will be further described below with reference to embodiments.
[0041] Example 1 (1) Glass fiber (SiO2 content above 99.9%) is coated with a sizing agent, twisted and wound to obtain a glass fiber yarn. The glass fiber yarn is sized and woven to obtain a glass fabric. (2) The glass blank cloth is subjected to a 10-second oscillating water wash (water temperature 50℃, rotation speed 200rpm) and a 10-second high-pressure water jet wash (water temperature 25℃, pressure 5.0kgf / cm²). -2 After drying for 30 seconds (at 50°C), fiberglass cloth I was obtained. Fiberglass cloth I had a moisture content of 0.05 wt%, a combustible content of 0.12 wt%, and an air permeability of 35 cm⁻¹. 3 / cm 2 / s; (3) Fiberglass cloth I was placed in a heating furnace and subjected to secondary heat treatment in four stages to obtain fiberglass cloth II: The heating furnace was introduced with air containing 0.05wt% moisture as heating gas 1 hour before the first stage of heating. The total time for the secondary heat treatment was 50 hours. The first stage was heated to 130℃ at a rate of 5℃ / min. The second stage was heated at 130℃. The third stage was heated to 320℃ at a rate of 5℃ / min. The fourth stage was heated at 320℃. The heating amount of the four stages was as follows: Q1=15%, Q2=10%, Q3=30% and Q4=45%. (4) Glass fiber cloth II was subjected to a first water washing and a second water washing and fiber opening, followed by silanization treatment to obtain ultra-low dielectric loss electronic grade glass fiber cloth; the first water washing and fiber opening was carried out in the fiber opening 1# water tank, and the pH of the water washing solution in the fiber opening 1# water tank was 8; the second water washing and fiber opening was carried out in the fiber opening 2# water tank, and the pH of the water washing solution in the fiber opening 2# water tank was 4; during the silanization treatment, the silane coupling agent (KH-570) was prepared into a uniformly dispersed coupling agent aqueous solution with a concentration of 0.05wt%, and acetic acid was added to adjust the pH to 3 before use. The moving speed (cloth speed) of glass fiber cloth II during the water washing and fiber opening and silanization treatment was 40m / min. The ultra-low dielectric loss electronic-grade glass fiber cloth produced was tested and found to have a dielectric loss (10GHz) of 0.0006, a strength of 110N / 25mm, an expansion coefficient of 1.0ppm / ℃, and no white spots on the surface.
[0042] Example 2 In step (2), the moisture content, combustible content, and air permeability of the fiberglass cloth I are controlled to be 0.20 wt%, 0.20 wt%, and 40 cm. 3 / cm 2 / s; The total time for the secondary heat treatment in step (3) is 120 hours. The first stage is heated to 135℃, the second stage is heated to 135℃, the third stage is heated to 350℃, and the fourth stage is heated to 350℃. The heating amount of the four stages is Q1=10%, Q2=5%, Q3=40% and Q4=45%. In step (4), the pH of the washing liquid in the fiber opening tank 1 is 7, and the cloth speed is 40m / min. Other steps are the same as in Example 1, and ultra-low dielectric loss electronic grade glass fiber cloth is obtained.
[0043] Example 3 In step (2), the moisture content of fiberglass cloth I is controlled to be 0.10 wt%, the combustible content to be 0.30 wt%, and the air permeability to be 50 cm. 3 / cm 2 / s; The total time for the secondary heat treatment in step (3) is 100 hours. The first stage is heated to 140℃, the second stage is heated to 140℃, the third stage is heated to 400℃, and the fourth stage is heated to 400℃. The heating amount of the four stages is Q1=15%, Q2=10%, Q3=35% and Q4=40%. The moisture content of the air used as heating gas is 0.02wt%. The pH of the washing liquid in the No. 2 water tank of fiber opening in step (4) is 4.5, and the cloth speed is 45m / min. The other steps are the same as in Example 1, and ultra-low dielectric loss electronic grade glass fiber cloth is obtained.
[0044] Example 4 In step (2), the moisture content of the fiberglass cloth I is controlled to be 0.30 wt%, the combustible content to be 0.50 wt%, and the air permeability to be 60 cm. 3 / cm 2 / s; In step (3), the first stage is heated to 150℃, the second stage is heated to 150℃, the third stage is heated to 500℃, and the fourth stage is heated to 500℃; the heating amount of the four stages is Q1=10%, Q2=10%, Q3=20% and Q4=60%; the moisture content of the air used as heating gas is 0.10wt%; in step (4), the pH of the washing liquid in the fiber opening 1# water tank is 9, the pH of the washing liquid in the fiber opening 2# water tank is 5, and the cloth speed is 50m / min; the other steps are the same as in Example 1, and ultra-low dielectric loss electronic grade glass fiber cloth is obtained.
[0045] Example 5 In step (2), the moisture content of the fiberglass cloth I is controlled to be 0.40 wt%, the combustible content to be 0.70 wt%, and the air permeability to be 30 cm. 3 / cm 2 / s; In step (3), the first stage is heated to 145℃, the second stage is heated to 145℃, the third stage is heated to 450℃, and the fourth stage is heated to 450℃; the heating amount of the four stages is Q1=15%, Q2=15%, Q3=30% and Q4=40%; the moisture content of the air used as heating gas is 0.04wt%; in step (4), the pH of the washing liquid in the fiber opening tank 1 is 9, and the cloth speed is 45m / min; the other steps are the same as in Example 1, and ultra-low dielectric loss electronic grade glass fiber cloth is obtained.
[0046] Example 6 In step (2), the moisture content of the fiberglass cloth I is controlled to be 0.50 wt%, the combustible content to be 0.90 wt%, and the air permeability to be 100 cm. 3 / cm 2 / s; In step (3), the first stage is heated to 150℃, the second stage is heated to 150℃, the third stage is heated to 630℃, and the fourth stage is heated to 630℃; the heating amount of the four stages is Q1=15%, Q2=10%, Q3=30% and Q4=45%; the moisture content of the air used as heating gas is 0.08wt%; in step (4), the pH of the washing liquid in the fiber opening tank #2 is 5, and the cloth speed is 50m / min; the other steps are the same as in Example 1, and ultra-low dielectric loss electronic grade glass fiber cloth is obtained.
[0047] The process parameters and performance parameters of the ultra-low dielectric loss electronic-grade glass fiber cloth in Examples 1-6 are shown in Table 1.
[0048] Table 1. Process parameters and performance parameters of ultra-low dielectric loss electronic-grade glass fiber cloth in Examples 1-6
[0049] Comparative Example 1 The pH of the washing solution in the No. 1 fiber-opening tank was changed to 5; the other steps were the same as in Example 2, and glass fiber cloth was obtained.
[0050] Comparative Example 2 The pH of the washing solution in the No. 2 water tank was changed to 7; the other steps were the same as in Example 2, and glass fiber cloth was obtained.
[0051] Comparative Example 3 The first stage heating temperature and the second stage heating temperature were both modified to 200℃; the other steps were the same as in Example 2, and glass fiber cloth was obtained.
[0052] Comparative Example 4 The heating temperature in the third stage and the heating temperature in the fourth stage were both modified to 700℃; the other steps were the same as in Example 2, and glass fiber cloth was obtained.
[0053] Comparative Example 5 The heating percentages for the four stages were modified to Q1=10%, Q2=5%, Q3=55%, and Q4=30%; the other steps were the same as in Example 2, and glass fiber cloth was obtained.
[0054] Comparative Example 6 The air permeability of fiberglass cloth I is controlled to be 10cm. 3 / cm 2 / s; other steps are the same as in Example 2, to obtain glass fiber cloth.
[0055] Comparative Example 7 The moisture content of glass fiber cloth I was controlled to be 1.0 wt%; other steps were the same as in Example 2, and glass fiber cloth was obtained.
[0056] Comparative Example 8 The combustible content in glass fiber cloth I was controlled to be 2.0 wt%; other steps were the same as in Example 2, and glass fiber cloth was obtained.
[0057] The process parameters and performance parameters of the glass fiber cloth in Comparative Examples 1-8 are shown in Table 2.
[0058] Table 2. Process parameters and performance parameters of glass fiber cloth in Comparative Examples 1-8
Claims
1. A manufacturing process for ultra-low dielectric loss electronic-grade glass fiber cloth, characterized in that... Includes the following steps: (1) Glass fiber yarn is sized and woven to obtain glass fabric; (2) The glass blank is heat-treated once to obtain glass fiber cloth I; (3) Glass fiber cloth I undergoes secondary heat treatment to obtain glass fiber cloth II; (4) Glass fiber cloth II is washed and split, and then silanized to obtain ultra-low dielectric loss electronic grade glass fiber cloth.
2. The manufacturing process of the ultra-low dielectric loss electronic-grade glass fiber cloth according to claim 1, characterized in that... In step (2), the combustible content of fiberglass cloth I is 0.1-1.0 wt%, and the combustibles include polyvinyl alcohol and starch; the moisture content of fiberglass cloth I is 0.01-0.5 wt%, and the air permeability is 30-100 cm. 3 / cm 2 / s.
3. The manufacturing process of the ultra-low dielectric loss electronic-grade glass fiber cloth according to claim 1, characterized in that... In step (2), the heat treatment is performed by cleaning and drying in sequence. The cleaning is performed by oscillating water washing and high-pressure water jet cleaning in sequence.
4. The manufacturing process of the ultra-low dielectric loss electronic-grade glass fiber cloth according to claim 1, characterized in that... The total time for the secondary heat treatment in step (3) is 50-120 hours. The secondary heat treatment is carried out in four stages. Taking the sum of the heating amount of the four stages as 100%, the heating amount of each stage is as follows: the heating amount of the first stage is 10-20%, the heating amount of the second stage is 5-15%, the heating amount of the third stage is 20-50%, and the heating amount of the fourth stage is 40-60%. The heating amount is the integral value of the heating temperature over time, and the unit of heating amount is ℃·h.
5. The manufacturing process of the ultra-low dielectric loss electronic-grade glass fiber cloth according to claim 4, characterized in that... The first stage is the heating stage, with a heating temperature of 130-150℃; the second stage is the heat preservation stage, with the heat preservation temperature being the same as the heating temperature in the first stage.
6. The manufacturing process of the ultra-low dielectric loss electronic-grade glass fiber cloth according to claim 4, characterized in that... The third stage is the heating stage, with a heating temperature of 300-650℃; the fourth stage is the heat preservation stage, with the heat preservation temperature being the same as the heating temperature in the third stage.
7. The manufacturing process of the ultra-low dielectric loss electronic-grade glass fiber cloth according to claim 1, characterized in that... The moisture content in the heating gas for the secondary heat treatment in step (3) is 0.01-0.10 wt%.
8. The manufacturing process of the ultra-low dielectric loss electronic-grade glass fiber cloth according to claim 1, characterized in that... In step (4), the fiber opening process involves sequentially performing a first-time and a second-time water washing process.
9. The manufacturing process of the ultra-low dielectric loss electronic-grade glass fiber cloth according to claim 8, characterized in that... The pH of the washing solution in the first water washing and fiber opening process is 7-9, and the pH of the washing solution in the second water washing and fiber opening process is 4-5.
10. The manufacturing process of the ultra-low dielectric loss electronic-grade glass fiber cloth according to claim 1, characterized in that... In step (4), the dielectric loss of the ultra-low dielectric loss electronic-grade glass fiber cloth at 10 GHz is 0.0004-0.0007.
Citation Information
Patent Citations
Production method of thin electronic-grade glass fiber cloth
CN115354494A